ANALISIS PENGARUH WORK-LIFE BALANCE DAN PENGEMBANGAN KARIER TERHADAP TURNOVER INTENTION KARYAWAN GENERASI Y DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada PT Bank Tabungan Negara Syariah Semarang) - Sismawati, Wiwik; Lataruva, Eisha (Diponegoro Journal of Management, 2020)
This study aims to analyze the influence of work-life balance and career development on generation Y employee’s turnover intention through job satisfaction as a mediator in PT Bank Tabungan Negara Syariah Semarang. The population used in this study are employees born between 1980 – 2000 or known as Y generation. Data were collected through questionnaires distributed to 55 emloyees. Measurement in the questionnaire used a seven point likert scale. The data analysis technique used in this study is IBM SPSS 23 with path analysis method. The data analysis used in this study include validity test, reliability test, classic assumption test, coefficient of determination test, F test, t test, and sobel test to determine the mediation effect.The results of this study show that the variable of work-life balance and career development have negative and significant effect on turnover intention. Work-life  balance and career development have positive and significant effect on job satisfaction. Meanwhile job satisfaction has negative and significant effect on turnover intention. In addition, this study shows that job satisfaction mediates the relationship between work-life balance and career development on turnover intention.